The Impact of Electronic Word-of-Mouth on Purchase Intention in Tripadvisor - Intansari, Devita Diana; Roostika, Ratna (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
This study aims to examine the effect of E-Wom among customers on purchase intentions on information media pages that provide information about products on Tripadvisor. This research uses purposive sampling technique. There were 270 respondents in this study. The model was analyzed by using structural equation modeling (SEM) with AMOS program. This study found that informative perceptions support E-Wom, persuasive perceptions support E-Wom, source expertise does not support E-Wom, trust in sources supports E-Wom, E-Wom usefulness supports e-Wom adoption, E-Wom adoption supports purchase intention, and the relationship between usefulness and decisions on purchase intention are mediated by E-Wom adoption.